Characterization and optimization of effluent dye removal using a new low cost adsorbent: Equilibrium, kinetics and thermodynamic study - Ezechi, E.H. (Institution of Chemical Engineers, 2015)
The adsorption capacity of a neglected adsorbent, Ageratum conyzoides leaf powder (ACLP), was investigated in this study for effluent dye removal. The adsorbent was characterized using FESEM, FTIR, BET, XRF, XRD and EDX. The combined effects of three independent variables (pH, dye concentration and adsorbent concentration) were evaluated in a batch study through Box Behnken model of the response surface methodology (RSM) for experimental design, analysis and process optimization. Dye removal efficiency was monitored at a predetermined contact time of 20 min. Adsorption kinetics was examined by first and second order rate models, Elovich and intraparticle diffusion models, while equilibrium study was examined by Langmuir and Freundlich isotherm models. At optimum conditions of pH 4 and adsorbent concentration of 0.06 g, dye removal efficiency exceeded 90 and was successfully optimized by RSM. Adsorption kinetics was described by pseudo second order kinetic model while equilibrium study was represented by Langmuir isotherm with maximum adsorption capacity of 192.4 mg/g. Preconcentration of MB onto ACLP was investigated and a factor of 108.3 was obtained. ACLP was regenerated and could be reused for a minimum of 20 cycles. Thermodynamic studies show that adsorption was spontaneous and exothermic. The results illustrate that Ageratum conyzoides leaf powder could be effectively utilized for effluent dye removal. Â© 2015 The Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.